2013
DOI: 10.1007/s00134-013-2870-7
|View full text |Cite
|
Sign up to set email alerts
|

The effects of increasing effective airway diameter on weaning from mechanical ventilation in tracheostomized patients: a randomized controlled trial

Abstract: Under the conditions of our protocol, deflating the tracheal cuff in tracheostomized patients shortens weaning, reduces respiratory infections, and probably improves swallowing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 22 publications
0
19
0
2
Order By: Relevance
“…To our knowledge, only one randomized trial has included high flow therapy in the protocol [41]. This was a single‐center study including 181 critically ill tracheostomy patients who were randomized to have the tracheal cuff deflated or not during spontaneous breathing trials.…”
Section: Clinical Datamentioning
confidence: 99%
“…To our knowledge, only one randomized trial has included high flow therapy in the protocol [41]. This was a single‐center study including 181 critically ill tracheostomy patients who were randomized to have the tracheal cuff deflated or not during spontaneous breathing trials.…”
Section: Clinical Datamentioning
confidence: 99%
“…To our knowledge, only one randomized trial has included high flow therapy in the protocol [41]. This was a singlecenter study including 181 critically ill tracheostomy patients who were randomized to have the tracheal cuff deflated or not during spontaneous breathing trials.…”
Section: Facilitating Weaning In Tracheostomized Patientsmentioning
confidence: 99%
“…Hernandez showed that deflating the tracheal cuff in tracheostomized patients shortens weaning, reduces respiratory infections, and probably improves swallowing. 38 Jubran et al in patients requiring PMV, showed that unassisted breathing through a tracheostomy (compared with pressure support) resulted in shorter median weaning time. 39 Verceles et al have shown that in patients under PMV, higher comorbidity burden is associated with increased risk of transfer to acute care.…”
Section: Namentioning
confidence: 99%